Correlation of the intended and referential meanings - Mykhaylenko, V. V.; Mихайленко, Валерій Васильович; Михайленко, В. В. (Одеса, 2015)
У фокусі дослідження знаходиться кореляція імплікативного значення (наміру) мовця під час виникнення висловлювання та інференціального значення слухача, яке формується в нього в процесі «прочитання» зазначеного висловлювання. Дієслова «manage» і «fail» слугують індикатором такої взаємодії.

The focus of study is the correlation implicative meaning (intention) of the speaker in the event of statements and inferential value of listening, which is formed in the course of his “perception” of this statement. Verbs “manage” and “fail” serve as an indicator of the interaction.
Mykhaylenko V. V. Correlation of the intended and referential meanings / V. V. Mykhaylenko // Одеський лінгвістичний вісник. – 2015. – Вип. 6. – Т.2. – С. 48-53.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; імплікативне значення; інференційне значення; мовець; слухач; семантика; корпус; дискурс; компонентна структура; implicative value; speaking; inference value; listener; semantics; corps; discourse; component structure